Building an empire in the Republic of Letters: Albrecht von Haller, Carolus Linnaeus, and the struggle for botanical sovereignty - Persson, Mathias (Circumscribere International Journal for the History of Science, 2016)
The eighteenth-century republic of letters was in many ways affected by strategies and concerns which fundamentally contradicted its core norms. This study analyses one such instance, the drawn-out conflict between the prominent botanists Albrecht von Haller and Carolus Linnaeus, by looking into the representations of Swedish and Hanoverian botany in the influential review journal Göttingische Anzeigen von gelehrten Sachen. At the same time, the article highlights an instance of the often cumbersome and complex transfer of scholarly teachings across national and linguistic borders, as well as the far from straightforward reception of a preeminent scholar in an important hub of knowledge, Göttingen, during the second half of the eighteenth century.